Characterization and mapping irrigation water quality of coconut groves in Coimbatore and Tiruppur districts of Tamil Nadu, India - Selvamani, V.; Duraisami, V.P. (Journal of Plantation Crops, 2014)
It is essential to characterize and map the irrigation water quality to foresee its adverse effect on soil health and productivity. A study was undertaken to generate irrigation water quality maps of coconut land cover in Coimbatore and Tiruppur districts of Tamil Nadu, India using geographic information system (GIS). Samples were collected from 110 geo-referenced collection sites. The irrigation water quality was assessed and thematic maps were developed. From the maps it was found that nearly 12 per cent area had poor quality irrigation water with respect to pH. Majority of the samples were safe and only around 10 per cent samples showed salinity hazard. Based on sodium adsorption ratio (SAR) the irrigation water of major area were in fair (53%) and poor (50%) classes. Irrigation water quality in terms of residual sodium carbonate (RSC) in nearly 42 per cent of the coconut land cover was under unsuitable class. The soluble sodium percentage (SSP) based classification showed good quality irrigation water in most of the area (97%). Around 51 per cent of the area was having irrigation water of unsatisfactory quality based on potential salinity. The permeability index (PI) of the irrigation water of 14 per cent area was found to be unsatisfactory.